O Eu e o Outro: a constituição da identidade política nos movimentos sociais urbanos - Diógenes, Glória Maria dos Santos (1989)
This dissertation has as its assumption the idea that political identity within social urban movements is constituted and reconstituted according to a process. It is based on research that was carried on the Comunidades Esclesiais de Base-CEBs in the poor area of Lagamar in the city of Fortaleza, state of Ceara. Lagamar was chosen as an “ideal model” considering the several relations between state and social movements. This dissertation focus on the struggle for a dwelling, facilities and urban services such which serves as a means for construction of a political awakening led by the movements within poor districts. A qualitative-directed study was developed. Interviews of great depth were used, applied not only to representatives of social urban movements of Lagamar, but also to State Government technicians and local mediators from the theological liberation movement. Besides the utilization of interviews, there were also the employment of in loco annotations of meetings, of lectures and of heated debates between community leaders and state officers. It was noted that there is a similarity between the movement’s subjects and those who “deny” the state’s presence, and both compound the political identity and field of alliances. A brief historical survey of the social movements of Fortaleza was carried on, including the community of Lagamar including its struggles, its organizational efforts and its actors. From these observations it was revealed the newness character of the Social Urban Movements in the production of an instituting political action field (according to Castoriadis). The expanding of the institutional field to include those “new” struggles amplifies the so-called public sphere to reach demands that were considered within the private realm only. It is concluded that the State plays a role in Lagamar conferring to the political identity other referents having as basis participative politics and the struggles for increasing the field of rights leading to improvements in citizenship.